2020
DOI: 10.3390/su12062490
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis for Earth-Fill Dam Seepage

Abstract: Earth-fill dams are the most common types of dam and the most economical choice. However, they are more vulnerable to internal erosion and piping due to seepage problems that are the main causes of dam failure. In this study, the seepage through earth-fill dams was investigated using physical, mathematical, and numerical models. Results from the three methods revealed that both mathematical calculations using L. Casagrande solutions and the SEEP/W numerical model have a plotted seepage line compatible with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 28 publications
(31 reference statements)
0
20
0
2
Order By: Relevance
“…Salmasi and Abraham [33] and Hosseinzadeh et al [8] used SEEP/W to predict the seepage from earthen channels at the Zayandeh-Rud irrigation channels, Iran. References [34][35][36][37] found that SEEP/W is a good tool to simulate the seepage from surface water to soil and vice versa. The model uses Darcy's Equation, which is expressed as:…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Salmasi and Abraham [33] and Hosseinzadeh et al [8] used SEEP/W to predict the seepage from earthen channels at the Zayandeh-Rud irrigation channels, Iran. References [34][35][36][37] found that SEEP/W is a good tool to simulate the seepage from surface water to soil and vice versa. The model uses Darcy's Equation, which is expressed as:…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Geometri bendungan meliputi kemiringan hulu dan hilir, lebar inti dan ketebalan inti berpengaruh terhadap kuantitas rembesan yang mengalir per satuan lebar, untuk bendungan inti zonal perbandingan horizontal terhadap vertikal sebesar 1:0,5 yang paling ideal (Al-Janabi et al, 2020). Koefisien permeabilitas (k), ketinggian air, kemiringan hulu (β), kemiringan hilir (α) dan lebar puncak mempengaruhi kecepatan aliran rembesan, peningkatan kecepatan aliran rembesan dapat meningkatkan gradien hidrolik (Tang et al, 2020).…”
Section: Nounclassified
“…In these cases, providing safety interactions is very effective in preventing the slope instability's occurrence [6]. The rapid drawdown in earth-fill dams is considered one of the main causes of slope failure in dam bodies [7,8] and a lack of attention to this matter eventually ends in dam failure [9]. Rapid drawdown in earthen dams demonstrates that the external water level drops so fast that impermeable soils within the earthen dam's slopes do not have sufficient time to drain.…”
Section: Introductionmentioning
confidence: 99%